Assessing financial and environmental impacts of management options - MacLeod, Neil.; McIvor, John.; Australia. Department of the Environment and Heritage; CSIRO Sustainable Ecosystems ([Canberra, A.C.T. : Dept. of the Environment and Heritage], 2006)
"Sustainable grazing in the rangelands requires new and different management practices. But what are the financial and environmental impacts of a new practice? They will not always be positive and may require trade-offs between financial and environmental benefits.Most decisions on grazing land management are made and implemented at the property level, and so assessment of ecological and economic trade-offs also needs to be made at this level.This publication describes a framework that land managers can use to help them decide how to balance environmental and economic considerations for their properties. The framework helps land managers assess production, economic and environmental impacts, and how they might trade off these impacts, before making decisions to change their management options.This publication describes a framework that land managers can use to help them decide how to balance environmental and economic considerations for their properties. The framework helps land managers assess production, economic and environmental impacts, and how they might trade off these impacts, before making decisions to change their management options. Six case studies are included to demonstrate how the framework can be used to model the financial and ecological impacts of different management practices in different rangeland regions." -- website.
Cover title.
"This paper is a summary of the report prepared for the Australian Government Dept. of the Environment and Heritage by CSIRO Sustainable Ecosystems."--Cover verso.
Bibliography: p. 40.
Also available in an electronic version on the Internet. Address as of 21/08/07: http://www.environment.gov.au/land/publications/rangelands-financial-environmental/pubs/financial-environmental.pdf
Keywords: Range management -- Australia; Biodiversity conservation -- Australia; Sustainable agriculture -- Australia